THE PLACE OF GOVERNMENTS IN THE POLITICAL SYSTEM OF GEORGIA DURING ITS TRANSFORMATION (1991-2003) - Бялоблоцький, З. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2012)
The article is dedicated to analyzing institutional and/or political peculiarities of Georgian constitutional system’s formation models in 1991-2003. The author determined economic, social, political, legal and historical backgrounds of post-Soviet political system transformation in Georgia; narrowly and/or broadly outlined government’s position in construction the models of power separation in Georgia; analyzed features of Georgian parliamentarism (1991), semi-presidentialism (1991-1995), presidentialism (1995-2003).